Federal home loan bank advances and commercial bank portfolio composition - W. Scott Frame; Diana Hancock; Wayne Passmore (Federal Reserve Bank of Atlanta, 2007)
This paper considers the role of Federal Home Loan Bank (FHLB) advances in stabilizing their commercial bank members' residential mortgage lending activities. Our theoretical model shows that using mortgage-related membership criteria or requiring mortgage-related collateral does not ensure that FHLB advances will be put to use for stabilizing members' financing of housing. Using panel vector autoregression (VAR) techniques, we estimate recent dynamic responses of U.S. bank portfolios to FHLB advance shocks, bank lending shocks, and macroeconomic shocks. Our empirical findings suggest that FHLB advances are just as likely to fund other types of bank credit as to fund single-family mortgages.
Keywords: G21; G18; G38; 330; advances; government-sponsored enterprises; GSE; portfolio shocks; panel VAR; Bankenpolitik; Kreditpolitik; Öffentliche Bank; Bausparkasse; Hypothek; Wohnungsbaufinanzierung; Wohnungsbaupolitik; USA